Development of phase doppler anemometer for measuring velocity and size distribution of paticulate materials - Wiwut Tanthapanichakoon (Chulalongkorn University, 2010)
คณะผู้วิจัย: วิวัฒน์ ตัณฑะพานิชกุล, หัวหน้าโครงการ ; หทัยชนก วานิชศรี, หัวหน้าโครงการวิจัยย่อย ; ธวัชชัย ชรินพาณิชกุล, รองหัวหน้าโครงการ ; Gerard Grehan, ที่ปรึกษาโครงการ ; ธนญชัย บุญนะที, ผู้ช่วยวิจัย